An exploratory analysis of employer branding in healthcare. Issue 1 (5th December 2018) - Berry, Alison; Martin, Jeanette
Abstract : Purpose: The purpose of this paper is to explore how large, public companies in the health industry communicatively engage in employer branding on career homepages. Design/methodology/approach: An exploratory content analysis of the career homepages ( N = 42; 8, 500) was conducted to analyze the communication of successful organizations in four realms of the public health-care industry to include Biotech ( n =10), Managed Health Care ( n = 8), Medical and Equipment Supplies ( n = 12) and Pharmaceuticals ( n = 12). Findings: The analysis revealed the following ten major themes of content: Worldview, Stakeholders, Environment, Excellence, Dedication, Aid, Unity, Advancement, Distinctiveness and Industry/Organization. Additionally, the results revealed that health-care employer branding often communicated about Stakeholders, Industry/Organization and Advancement. Research limitations/implications: The results of this study aid researchers in understanding the foundational content of employee branding efforts in the health industry. Practical implications: The results assist practitioners in understanding how different health-care industries and organizations engage in employer branding on career homepages. Originality/value: The results of this study function to both confirm previous findings related to employer branding and extend research on employer branding into the career homepages of organizations in the health-care industry.